2019
DOI: 10.26682/sjuod.2019.22.2.27
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence And Risk Factors of Toxoplasmosis among Undergraduate Female Students of University of Duhok

Abstract: Toxoplasmosis is a zoonotic infection caused by Toxoplasma gondii parasite. University female students are at the age of childbearing and their status of T. gondii infection is important. Thus, early detection and therapy are of extraordinary importance. Therefore, this study aimed to find out the seroprevalence of Toxoplasma gondii infection among undergraduate female students of University of Duhok. A cluster stratified sampling procedure was used for each college in Duhok University and a proportionate numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In Erbil, rates of 37.5% and 34.18% for IgG and 9.13% and 10.86% for IgM, respectively, have been reported [ 21 ]. In Duhok city, Ramadhan and Sarkees have conducted a seroprevalence survey among female undergraduate students [ 22 ], and Salih and colleagues [ 23 ] conducted a study among healthy women and reported rates of 44.4% and 35.61% for IgG and 11.1% and 0.76% for IgM, respectively, while much higher rates for both IgG and IgM at 51.5% and 45%, respectively, have been reported in Kirkuk city [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Erbil, rates of 37.5% and 34.18% for IgG and 9.13% and 10.86% for IgM, respectively, have been reported [ 21 ]. In Duhok city, Ramadhan and Sarkees have conducted a seroprevalence survey among female undergraduate students [ 22 ], and Salih and colleagues [ 23 ] conducted a study among healthy women and reported rates of 44.4% and 35.61% for IgG and 11.1% and 0.76% for IgM, respectively, while much higher rates for both IgG and IgM at 51.5% and 45%, respectively, have been reported in Kirkuk city [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding agrees with a study conducted in Cameroon, which demonstrated an association between marital status and IgM seropositivity [ 51 ]. On the other hand, Ramadhan and Sarkees, in Duhok, report higher seroprevalence of anti- Toxoplasma IgM among single undergraduate female students than married ones [ 22 ].…”
Section: Discussionmentioning
confidence: 99%